Pemecatan Anggota Partai Politik Karena Menjadi Pengurus Organisasi Kemasyarakatan - Putri, Gusti Agung (Acta Comitas : Jurnal Hukum Kenotariatan, 2018)
Members of have the right submitted by political parties as candidates for Legislative Assembly in accordance with what is meant by article 12 of Law Number 2 of 2008 jo Law Number 2 of 2011, that political parties have the right to nominate candidates to fill the membership of the Nation Assembly and the Regional Local Assembly in accordance with the legislation; propose a change of time between its members in the Nation Assembly and the Local Assembly in accordance with the legislation. Instead members of political parties must submit and comply with the provisions in Law No. 2 of 2008 jo Law No. 2 of 2011 and the articles of association and bylaws of political parties, accompanied by good sanctions from Law No. 2 of 2008 jo Law No. 2 of 2011 and sanctions on political party organizations. This means that members of a political party can be dismissed from their membership if they become members of other political parties. Substitution between time as a member of the House of Representatives is permitted as long as the interim replacement is in accordance with the prevailing laws and regulations, including participating as members of other Political Parties. Ishak Liputo is listed as the administrator of the Democratic National Community Organization which is not listed as a political party, but Isaac Liputo was replaced through a replacement between times because he was the administrator of a community organization. But in this case Ishak Liputo was fired because he had previously served as administrator of the National Democratic Community Organization before the Organization was officially inaugurated as a Political Party. Research shows the dismissal of Isaac Liputo from membership of the Golongan Karya Political Party because of being the administrator of the National Democratic Community Organization (Nasdem) in terms of Law No. 2 of 2008 jo Law No. 2 of 2012 concerning Political Parties is not appropriate, because: Ishak Liputo became the administrator of the Nasdem Mass Organization, which has not been in the form of a party, so it cannot be said to be a member of a political party. Liputo when warned by the Golkar Party's Management of his actions as a Nasdem administrator, has resigned, so he is no longer a Nasdem administrator.